Overview of carbon and nitrogen catabolite metabolism in the virulence of human pathogenic fungi - Ries, Laure Nicolas Annick (Mol Microbiol, 2017)
It is estimated that fungal infections, caused most commonly by Candida albicans, Aspergillus fumigatus and Cryptococcus neoformans, result in more deaths annually than malaria or tuberculosis. It has long been hypothesized the fungal metabolism plays a critical role in virulence though specific nutrient sources utilized by human pathogenic fungi in vivo has remained enigmatic. However, the metabolic utilisation of preferred carbon and nitrogen sources, encountered in a host niche-dependent manner, is known as carbon catabolite and nitrogen catabolite repression (CCR, NCR), and has been shown to be important for virulence. Several sensory and uptake systems exist, including carbon and nitrogen source-specific sensors and transporters, that allow scavenging of preferred nutrient sources. Subsequent metabolic utilisation is governed by transcription factors, whose functions and essentiality differ between fungal species. Furthermore, additional factors exist that contribute to the implementation of CCR and NCR. The role of the CCR and NCR-related factors in virulence varies greatly between fungal species and a substantial gap in knowledge exists regarding specific pathways. Further elucidation of carbon and nitrogen metabolism mechanisms is therefore required in a fungal species- and animal model-specific manner in order to screen for targets that are potential candidates for anti-fungal drug development.